Philosophy of religion and the African American experience : conversations with my Christian friends - McClendon, John H. (Value Inquiry Book Series, 2017)
Most white philosophers of religion generally presume that philosophy of religion is based on what is a false universality; whereby the white/Western experience is paradigmatic of humanity at-large. The fact remains that Howard Thurman, James H. Cone and William R. Jones, among others, have produced a substantial amount of theological work quite worthy of consideration by philosophers of religion. Yet this corpus of thought is not reflected in the scholarly literature that constitutes the main body of philosophy of religion. Neglect and ignorance of African American Studies is widespread in the academy. By including chapters on Thurman, Cone and Jones, the present book functions as a corrective to this scholarly lacuna.